Using LLTO with vertically aligned and oriented structures to improve the ion conductivity of composite solid-state electrolytes. (December 2022) - Li, You; Zhai, Yuxin; Xu, Shuxin; Tang, Mulan; Zhang, Shuchao; Zou, Zhengguang
Abstract: Replacing organic liquid electrolyte with solid electrolyte is considered to be the most promising method to solve the safety problem of lithium battery. However, the low ionic conductivity limits the practical application of solid electrolyte. Solid electrolyte Li3x La2/3−x TiO3 (LLTO) with vertically aligned and oriented structures was successfully prepared by improved electrospinning method. The ionic conductivity of the composite solid electrolyte with vertical aligned and oriented structures is as high as 4.67 × 10 −4 S/cm at room temperature (25 ℃). The sintering process system of LLTO with vertical aligned and oriented structures was also determined. The vertically oriented composite solid-state electrolyte has wide electrochemical window (0–6 V) and high Li + transference number（0.796）. At a current density of 0.1 mA/cm 2, the Li/CSSE/Li symmetrical lithium battery has a constant current cycle of more than 700 h at room temperature. The experimental results of Li + stripping experiment also show that the composite solid-state electrolyte filled with organic materials has good electrochemical stability. Based on the above experimental results, it is proved that this vertically arranged composite solid-state electrolyte framework plays an important role in constructing fast ion conduction channels and improving ion conductivity. Graphical Abstract: ga1 Highlights: For the first time, the composite solid electrolyte based on LLTO with aligned and ordered structure was prepared by electrospinning. Transverse crystal structure has an important influence on the electrical conductivity of Li+. The ionic conductivity of the electrolyte is almost doubled, which was higher than the composite electrolyte with disordered structure.